2014
DOI: 10.1055/s-0034-1390494
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Suppresses Intra-abdominal Fatty Acid Synthesis in Ovariectomized Rats

Abstract: Ovarian hormone loss is associated with a shift in fat distribution to intra-abdomin al adipose tissue (intra-AAT) depots and with lipid metabolism disorders, which predisposes individuals to developing insulin resistance. Resistance training (RT) prevents increases in intra-AAT after ovarian hormone loss. However, the molecular mechanisms underlying these changes remain unclear. We investigated the effects of ovariectomy and RT on gene expression related to lipogenesis and fat oxidation in the intra-AAT of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Thus, postmenopausal women show an increase in AT mass, especially for visceral fat, contributing to deficient vascularization in this tissue 4. Additionally, estrogen plays an important role in body composition by suppressing WAT accumulation through reductions in fatty acids, triglyceride synthesis and lipogenesis 4,18. In our study, ovariectomy resulted in increases in both body mass and adipocyte hypertrophy in VAT.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Thus, postmenopausal women show an increase in AT mass, especially for visceral fat, contributing to deficient vascularization in this tissue 4. Additionally, estrogen plays an important role in body composition by suppressing WAT accumulation through reductions in fatty acids, triglyceride synthesis and lipogenesis 4,18. In our study, ovariectomy resulted in increases in both body mass and adipocyte hypertrophy in VAT.…”
Section: Discussionmentioning
confidence: 48%
“…Recent studies have indicated that Rt is beneficial for skeletal muscle, bones and liver 17,18,35. Previous studies conducted by our group have shown that Rt is able to decrease fat accumulation and deposition in the livers of Ovx rats 36 and to reduce the gene expression of molecules related to lipogenesis 17.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Is well established in the literature that RT promotes irisin release, and also increases cellular thermogenesis and reduces fat storage by suppressing formation of new adipocytes [19,20,[39][40][41]. Therefore, maintaining optimal irisin concentrations seems to be important, especially in our ovariectomy model, which has strong evidences of being a precursor of obesity and other metabolic disorders [42][43][44][45]. We found that the Ovx-Sed group presented similar values of irisin levels when compared to Sham-Sed group (Figure 3).…”
Section: Ovariectomymentioning
confidence: 94%